RELEVANSI KURIKULUM EKONOMI SYARIAH IAIN LHOKSEUMAWE TERHADAP SUMBER DAYA MANUSIA PADA LEMBAGA KEUANGAN SYARIAH - Juliana Putri (Faculty of Islamic Economics and Business, IAIN Lhokseumawe, 2019)
This study aims to explain the relevance of the syariah economic curriculum that is applied to the Islamic economics department of the Islamic economics and business faculty of IAIN Lhokseumawe in preparing the human resources needed by the Lhokseumawe Islamic financial institutions and to explain the absorption and absorption of alumni of sharia economic jueusan in the world of work. With the results of the study that the relevance of Islamic economics curriculum to human resources in Islamic financial institutions the criteria are generally the parameters of employee / employee recruitment in Islamic financial institutions in Lhokseumawe City tend to be in soft skills assessment (performance and psychological). The unavailability of professional graduates in the field of sharia economics causes the need for professional staff in sharia business to continue to be met by converting from conventional workers, namely that many graduates of general tertiary institutions can fill formation in Islamic financial institutions, even though those who do not have qualified knowledge in the field of sharia economics . The distribution of Islamic Economics graduates in financial institutions is not optimally absorbed in financial institutions, even in Islamic Commercial Banks, the absorption is 0% at BNI Syariah Bank, Aceh Syariah Bank Samudera Branch and Merdeka Branch, Muamalat Bank, BRI Syariah. 30% absorption is absorbed at Baitul Qirat Afdhal Lhokseumawe Branch. Of the 23 employees 9 of them were graduates of the Shariah Economics of the Lhokseumawe branch. Bank Syariah Mandiri Lhokseumawe Branch of 32 Employees 2 of whom are graduates of the Sharia economy of the Lhokseumawe branch, as well as the FIF Syariah and Baitul Mal absorbed by 2 graduates of Islamic economics.